PENINGKATAN KEMAMPUAN KOMUNIKASI DAN DISPOSISI MATEMATIS SISWA MELALUI PEMBELAJARAN KOPERATIF TIPE JIGSAW DI SMP MUHAMMADIYAH KOTA PADANGSIDIMPUAN - Masdelima Azizah Sormin (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
This  research  aims  to  determine:  (1)  the  improvement  of mathematical  communication   skill   and   disposition   of students  who  received  jigsaw  cooperative  learning  and conventional learning, (2) the interaction between learning model   and   prior   knowledge   of   the   mathematical communication   skill   and   student   disposition.   The research  conducted  in  SMP  Muhamadiyah Padangsidimpuan   city.   The   researchtype   is   quasi-experimental  pre-test-post-test  control  group  design.  The population  in  this  study  was  all  eighth-grade  students  of SMP  Muhamadiyah  Padangsidimpuan  city  and  sample was  30  students  in  class  VII-3  as  an  experimental  class and   30   students   in   class   VII-1   as   a   control   class. Sampling   was   carried   out   through   purpose   sampling technique.  The  research  instrument  used  is  a mathematical   communication   skill   test,   questionnaire, student  disposition.  The  hypothesis  testing  in  this  study usedtwo  way  ANOVA.  The  results  showed  that  (1)  the improvement  of  mathematical  communication  skill  who received   jigsaw   cooperative   learning   is   higher   than conventional learning. The average of communication skill improvementused  jigsaw  cooperative  learning  and conventional learning respectively 0.64 and 0.65, and the improvement of student disposition respectively 0.43 and 0.45.  (2)  There  is  interaction  between  learning  and  prior knowledge   of   mathematical   communicatin   skill   and student disposition.